The Effect of Work-Family Conflict, Work Overload, and Perceived Organizational Support towards Work Stress and Its Impact on Turnover Intentions in the Private Bank Employees - Sunatar, Bambang (Universitas Mercu Buana, 2024)
Objectives: The objective of this research is to determine how work-family conflict, work overload, and perceived organizational support affect work stress and subsequently influence turnover intentions in private bank employeesMethodology: The study employs a quantitative approach to test known hypotheses and involves collecting data via questionnaires from 120 participants in Sorong, West Papua, Indonesia. The data is analyzed using a structural equation model (SEM) with the aid of smart PLS and 100 samplesFinding: The results indicate that work-family conflict and work overload have significant positive effects on work stress and turnover intentions. Additionally, perceived organizational support has a significant positive impact on both work stress and turnover intentions. The study further finds that work stress mediates the relationship between work-family conflict, work overload, perceived organizational support, and turnover intentions. Therefore, organizations must address work-family conflict, and work overload to provide perceived organizational support to reduce work stress and turnover intentions among their employeesConclusion: According to this research, the implications are that managers should implement measures to minimize work-family conflicts and workload to enhance employee well-being and reduce their intentions to leave the organization and the need to ensure that employees perceive support from the organization in different aspects such as compensation, promotion, and recognition